Effect of Adding Pectin on The Quality of Red Dragon Fruit (Hylocereus polyrhizus) Sheet Jam - Zanaria; Mahrus; Zulkifli, Lalu; Rasmi, Dewa Ayu Citra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Dragon fruit has a high water content and a limited shelf life. Dragon fruit has the potential to be used as a raw material for food processing, one of which is jam. Dragon fruit contains pectin which functions as a gelling agent in jam. This research aims to determine the addition of pectin with different concentrations on the quality of red dragon fruit jam sheets. This research is an experimental study using a completely randomized design (CDR) with four treatments and four replications. Data were analyzed using Analysis of Varience (ANOVA) to obtain Duncan New Multiple Range Test (DNMRT) results at level 5%. The research results showed that the effect of pectin with different concentrations provided significant differences (P<0.05) on water content, ash content, sucrose content, crude fiber content, total dissolved solids, degree of acidity (pH), and organoleptic tests. The addition of 0.75% pectin affects the chemical, physical and organoleptic properties of Red Dragon Fruit Jam. Chemical ingredients consist of water, ash, sucrose content, crude fiber content, total dissolved solids, acidity degree (pH), and physical characteristics including taste, color, aroma and texture. A total of 25 panelists liked the organoleptic properties. In conclusion, the effect of adding pectin on the quality of the best jam product is P3 (0.75% pectin addition) so it is more acceptable based on its character and organoleptic properties.